Valuation of CTT : Correios de Portugal S.A. - Nunes, João Diogo Oliveira Pereira de Seixas (2020)
The purpose of this thesis was to evaluate a listed company to demonstrate and use the knowledge gathered during the master. The selected company was CTT – Correios de Portugal, S.A. due to several reasons. Firstly, this is a Portuguese company, with long history and has always played an important role in Portuguese society. Secondly, it has operations in other countries than Portugal. Thirdly, it used to be owned by Portuguese Government and only recently became listed in Lisbon Stock Exchange. Finally, even though the main source of revenues (Mail) is facing severe challenges, as e-substitution and other factors have a negative impact on mail volumes, CTT’s bet in the financial services sector, and more recently the Postal Bank, seemed to be good strategy. Before getting to CTT’s value assessment, the author goes through the academic theory on the most relevant valuation methodologies for this valuation exercise. Then, detailed descriptions of the company and postal sector were provided, as well as the assumptions and forecasts. In the end, the author opted for assessing CTT business, excluding the postal bank, with a WACC based discounted cash flow model. Then, decided to value the postal bank separately using a FTE methodology, discounted at cost of equity. As means of conclusion, the author ends this thesis by presenting a price target and respective recommendation, and comparing his outcome with that of an investment bank’s research note (BPI).